2018
DOI: 10.1038/s41598-018-26208-8
|View full text |Cite
|
Sign up to set email alerts
|

North American domestic pigs are susceptible to experimental infection with Japanese encephalitis virus

Abstract: Japanese encephalitis virus (JEV) is a mosquito-borne flavivirus that is capable of causing encephalitic diseases in children. While humans can succumb to severe disease, the transmission cycle is maintained by viremic birds and pigs in endemic regions. Although JEV is regarded as a significant threat to the United States (U.S.), the susceptibility of domestic swine to JEV infection has not been evaluated. In this study, domestic pigs from North America were intravenously challenged with JEV to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 44 publications
(59 reference statements)
3
59
0
Order By: Relevance
“…Our in vitro results complements previously published in vivo findings, which can explain the high efficiency of JEV infection of pigs via the oronasal route and are in line with different experiments which showed oronasal shedding several days beyond the end of viremia, and they additionally can explain the detection of high levels of JEV RNA in nasal mucosa, which can last up to 10 days after challenge ( 8 12 ). The in vivo relevance of the presented data is further supported by the observation that after oronasal JEV challenge of immune pigs, it is possible to detect the challenge virus in oronasal swabs for several days in the absence of detectable viremia ( 9 ), pointing to a local cellular source for virus replication, which is also supported by a recent study in which the larger JEV RNA amount was detected in nasal mucosa ( 11 ).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our in vitro results complements previously published in vivo findings, which can explain the high efficiency of JEV infection of pigs via the oronasal route and are in line with different experiments which showed oronasal shedding several days beyond the end of viremia, and they additionally can explain the detection of high levels of JEV RNA in nasal mucosa, which can last up to 10 days after challenge ( 8 12 ). The in vivo relevance of the presented data is further supported by the observation that after oronasal JEV challenge of immune pigs, it is possible to detect the challenge virus in oronasal swabs for several days in the absence of detectable viremia ( 9 ), pointing to a local cellular source for virus replication, which is also supported by a recent study in which the larger JEV RNA amount was detected in nasal mucosa ( 11 ).…”
Section: Discussionsupporting
confidence: 76%
“…While JEV is also found in tonsils ( 8 , 9 , 12 ), immune animals’ tonsils were found to be protected from infection, indicating that this organ is infected only following viremia ( 9 ) and would therefore not represent the point of JEV entry. On the other hand, a recent study demonstrated the presence of viral RNA in the nasal epithelium as well as in the olfactory neuroepithelium ( 11 ). We therefore investigated whether the nasal epithelium can be infected from the apical surface and whether this infection would cause both apical and basolateral virus shedding.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas mosquito distribution and host density are probably low in airport areas (Mier‐y‐Teran‐Romero, Tatem, & Johansson, ), where the risk of JEV introduction is the highest (as determined in previous steps of the framework), it is highly uncertain in other regions across the at‐risk area considered in this RA. Moreover, a recent study has confirmed that North American domestic pigs are susceptible to experimental infection with JEV (Park et al., ), which would allow for virus transmission (and establishment). Generating spatial maps displaying the location of airports with international flights arriving from JEV endemic countries in Asia, as well the distribution of pig populations in the continental US, could benefit surveillance efforts and further aid in determining the risk of JEV transmission (and further establishment) in the US.…”
Section: Discussionmentioning
confidence: 89%
“…Despite being the primary mammalian amplifying host for JEV (6), meta-regression modeling did not identify domestic pigs as the host species with the highest proportion of JEV infection (7). Nonetheless, North American domestic pigs were shown to be susceptible to JEV experimental infection (23)(24)(25) and although the majority of pigs in the US are housed indoors, commercial housing does not preclude mosquito exposure (26)(27)(28).…”
Section: Lessons Learned Regarding Virus-vector-host Interactionsmentioning
confidence: 99%